lim x tends to infinity 2/x-3=0
Answers
Answered by
1
Lim
X ->infinity 2/x-3
= 2/x( 1 - 3/x ) Here we take the HCF highest common factor of x.
Since 3/x equals zero
= 2/x (1)
= 2/x
=0
Where 2/x equals zero
X ->infinity 2/x-3
= 2/x( 1 - 3/x ) Here we take the HCF highest common factor of x.
Since 3/x equals zero
= 2/x (1)
= 2/x
=0
Where 2/x equals zero
Similar questions
Social Sciences,
9 months ago
Science,
9 months ago
Computer Science,
9 months ago
Social Sciences,
1 year ago
English,
1 year ago
Psychology,
1 year ago
English,
1 year ago